Metal Ions Doping for Boosting Luminescence of Lanthanide-Doped Nanocrystals - Pei, Shihao; Ge, Xiaoqian; Sun, Lining (Frontiers in Chemistry, 2020)
With the developing urge for the better performance of luminous materials, the lanthanide doped nanocrystals have been widely studied for their unique luminescence properties like narrow bandwidth emission, excellent chemical stability and photostability, the adjustable emission color, high signal-to-background ratio, deeper tissue penetration with less photo-damage, and low toxicity, etc., which triggered the enthusiasm for research on the broad applications of lanthanide doped nanocrystals in bioimaging, anti-counterfeiting, biosensing, cancer diagnosis and treatment. Simultaneously, there are considerable progress have been made in the past decades, whereas the low upconversion luminescence efficiency has been the hindrance in achieving further progress. It is necessary to summarize the recently relevant literature and find solutions to improve the efficiency. The latest experimental and theoretical studies related to the deliberate design of rare earth luminescent nanocrystals have, however, showed the development of metal ion doped approaches to enhance the luminescent intensity. Host lattice manipulation can enhance the luminescence through increasing the asymmetry, which improves the probability of electric dipole transition; and the energy transfer modulation offers a reduced-cross-relaxation pathway to improve the efficiency of energy transfer. Based on the mechanisms of host lattice manipulation and energy transfer modulation, a wide range of enhancement at all wavelength or even within a particular wavelength has been accomplished with the enhancement up to hundred times. In this mini-review, we present the strategy of metal ions doped lanthanide nanocrystals to cope with the issue of enhancing luminescence, overview the advantages and tricky challenges in boosting the luminescence, and provide potential trend of future study in this field.